Reverse engineering to achieve maintainable WWW sites - Boldyreff, C.; Kewish, R. (Proceedings Eighth Working Conference on Reverse Engineering, 2001)
The growth of the World Wide Web and the accelerated development of web sites and associated web technologies has resulted in a variety of maintenance problems. The maintenance problems associated with web sites and the WWW are examined. It is argued that currently web sites and the WWW lack both data abstractions and structures that could facilitate maintenance. A system to analyse existing web sites and extract duplicated content and style is described here. In designing the system, existing reverse engineering techniques have been applied, and a case for further application of these techniques is made in order to prepare sites for their inevitable evolution in future.